Popularity of Fingerstyle Music Towards Common Music Practitioners and Enthusiasts - Abdul Rachman; Alvriza Mohammed Fadly (Cinematology: Journal Anthology of Film and Television Studies, 2023)
Fingerstyle is a guitar performing technique and a music style which has high popularities in various circles, especially for music practitioners and enthusiasts in general. Fingerstyle is another term of solo guitar which is a guitarist plays the instrument independently with a special arrangement. Because of Fingerstyle musicality has very diverse innovations and sound processing, Fingerstyle is now well-known and studied by several music practitioners and enthusiasts in general. This study uses quantitative descriptive method. Data collection technique uses questionnaire in google form, and this study approach uses survey method. The result of this study is to measure and rate how far the popularities of fingerstyle consisting of musicality popularity, diverse techniques, and fingerstyle musician can influence music practitioners and enthusiasts in general.